Isolation and Identification of Flavonoid Compounds and Antibacterial Activity Test of the Canyere Badak Plant (Bridelia glauca Blume) (Phyllanthaceae) - Lamek Marpaung; Ade Theresia Ulina Lumban Toruan (Journal of Chemical Natural Resources, 2023)
Flavonoid compounds from the stem bark of the Canyere Badak plant (Bridelia glauca Blume) have been isolated. 2500 g of Canyere Badak plant stem bark was macerated by methanol, and the methanol extract dissolved in distilled water. The distilled water solution was extracted by partitioning with ethyl acetate repeatedly until negative to 5% FeCl3. The ethyl acetate extract was dissolved in methanol and extracted by partitioning with n-hexane until the n-hexane layer was transparent. The methanol extract was analyzed by thin layer chromatography and separated by column chromatography with a stationary phase of silica gel and a mobile phase of chloroform: methanol (90:10; 80:20; 70:30; 60:40) v/v. Fractions 148-174 were purified by preparative thin layer chromatography using benzene: acetone (80:20) v/v eluent to produce a brownish yellow paste of 10 mg at Rf value of 0,66 using chloroform: methanol (80:20) v/v  as eluent. Based on the analysis of the UV-visible spectrophotometer, it had a wavelength (Î» max) of 275 nm. The FT-IR spectrum shows the presence of OH, C=C aromatic, C=O ketones, C-H, C-O-C and C-O groups. The proton Nucleus Magnetic Resonance Spectrum (1H-NMR) indicates the presence of H-2’ & H-6’ protons, H-3’ & H-5’ protons and methoxy protons. Based on the data analysis and interpretation, the isolated compound was a flavonoid of the flavanones group. The antibacterial activity of total flavonoids was determined by agar disk diffusion against Staphylococcus aureus and Escherichia coli bacteria. The results showed that total flavonoids strongly inhibited the growth of Staphylococcus aureus and Escherichia coli bacteria with MIC (Minimum Inhibitory Concentration) value at a concentration of 100 mg/mL obtained a clear zone of 9.5 mm against Staphylococcus aureus bacteria and at a concentration of 100 mg/mL obtained a clear zone of 12.15 mm against Escherichia coli bacteria.